Abolishing the frontier: (De)colonizing 'public' education. (24th March 2021) - Luke, Nikki; Heynen, Nik
ABSTRACT: In this paper, we situate the public university as a frontier where structures of settler colonialism, racialization, and citizen formation are both created and contested. We use the historical-geographical position of the University of Georgia, the first public land grant university chartered in the United States, to consider the broader implications of the settler-native-slave triad in the history of public higher education. We use these historical insights to expand upon W. E. B. Du Bois' notion of abolition democracy and Indigenous discussions of decolonization. We animate the possibilities of abolition democracy informing public higher education through three interventions that question the ways in which people within public institutions of higher education can destabilize and work to democratize the systems that enclose land, labor, and education as private property.